Unity and Diversity in Sociologie (Unité et Diversité en Sociologie). Transactions of the Sixth World Congress of Sociology (Actes du Sixième Congrès Mondial de Sociologie). Vol. II - Uribe Villegas, Óscar (Revista Mexicana de Sociología, 1968)
reseña